Safety and efficacy of pomalidomide plus low-dose dexamethasone in STRATUS (MM-010): a phase 3b study in refractory multiple myeloma - Dimopoulos, Meletios A.; Goldschmidt, Hartmut (Blood, 2016)
Patients with relapsed and/or refractory multiple myeloma (RRMM) have poor prognosis. The STRATUS study assessed safety and efficacy of pomalidomide plus low-dose dexamethasone in the largest cohort to date of patients with RRMM. Patients who failed treatment with bortezomib and lenalidomide and had adequate prior alkylator therapy were eligible. Pomalidomide 4 mg was given on days 1-21 of 28-day cycles with low-dose dexamethasone 40 mg (20 mg for patients aged >75 years) on days 1, 8, 15, and 22 until progressive disease or unacceptable toxicity. Safety was the primary end point; secondary end points included overall response rate (ORR), duration of response (DOR), progression-free survival (PFS), and overall survival (OS). Among 682 patients enrolled, median age was 66 years, and median time since diagnosis was 5.3 years. Median number of prior regimens was 5. Most patients were refractory to both lenalidomide and bortezomib (80.2%). Median follow-up was 16.8 months; median duration of treatment was 4.9 months. Most frequent grade 3/4 treatment-emergent adverse events were hematologic (neutropenia [49.7%], anemia [33.0%], and thrombocytopenia [24.1%]). Most common grade 3/4 nonhematologic toxicities were pneumonia (10.9%) and fatigue (5.9%). Grade 3/4 venous thromboembolism and peripheral neuropathy were rare (1.6% each). The ORR was 32.6%, and the median DOR was 7.4 months. Median PFS and OS were 4.6 months and 11.9 months, respectively. We present the largest trial to date evaluating pomalidomide plus low-dose dexamethasone in patients with RRMM, further confirming that this regimen offers clinically meaningful benefit and is generally well tolerated. www.Clinicaltrials.gov identifier NCT01712789.
Gesehen am 04.01.2019